Path Planning Simulation of 6-DOF Manipulator. (June 2020) - Zhang, Junhao; Yang, Xingbo; Li, Yawei; Zhang, Ningbo
Abstract: With the development of automation and intelligence in manufacturing industry, industrial robots have become an important part of intelligent chemical plants. In practical application, all functions implemented are realized by manipulator. Facts have proved that reasonable path planning for the manipulator is helpful to reduce the loss and impact of mechanical parts during operation, greatly improve the service life of the manipulator, and also help to improve the control accuracy of the manipulator of the robot. In this paper, the six-degree-of-freedom manipulator is taken as the research object, and the motion path planning scheme of the manipulator is designed, which is verified by PVDF material grabbing simulation experiments. The results show that the motion path of the manipulator designed in this paper takes less time than the shortest path to grab materials, and the operation accuracy is higher.